The Reformist Thought of Muhammad Ali Jinnah and Its Implications for Islamic Education in Pakistan - Said Usman Umar (Yayasan Rahmat Islamiyah, 2026)
This study examines the historical development of Islam in Pakistan and the reformist political thought of Muhammad Ali Jinnah within the broader context of modern Islamic political discourse. The establishment of Pakistan in 1947 represents one of the most significant political transformations in the modern Muslim world, emerging from the interaction between colonialism, nationalism, religious identity, and constitutional development. Muhammad Ali Jinnah, as the principal architect of Pakistan, introduced a political vision that sought to reconcile Islamic identity with constitutional democracy, the rule of law, pluralism, and modern statehood. Previous studies have generally examined Pakistan's history, Jinnah's political leadership, or Islamic nationalism independently, leaving limited discussion that integrates these dimensions within a comprehensive analytical framework. This research employs a qualitative library research approach using historical and political analysis. Data were collected from primary historical documents, Jinnah's speeches, official political documents, and contemporary academic literature concerning Pakistan, Islamic political thought, and modern Muslim nationalism. The findings indicate that the creation of Pakistan was not merely a religious movement but also a political response to colonial governance, communal tensions, and the demand for Muslim political representation in British India. Furthermore, the study reveals that Jinnah envisioned Pakistan not as a formal theocratic state but as a modern Muslim nation grounded in constitutional governance, democratic principles, religious freedom, and equal citizenship. Although his ideas have been criticized by both Islamist and liberal scholars, Jinnah's political thought continues to provide an important framework for understanding the relationship between Islam, democracy, nationalism, and the modern nation-state.